Effects Of Fin Length And Fin Valley On The Performance Of Bus Duct Conductor - Hooi, Khey Herng (Universiti Sains Malaysia, 2022)
There are many ways to conduct electricity and one of the alternative methods of transmitting electricity is by using bus duct conductor. In commercial and industrial sectors, bus duct conductor is used to supply electricity to power cables or cable buses. However, the demand for high-performance thermal heat sinks is growing and conventional designs are no longer adequate. Hence, the objective of this study is to analyse the effects of fin length and fin valley on the performance of bus duct conductor using Ansys Fluent. Following the verification of the simulation and experiment results, the results showed that it had a percentage difference of 4.57 %. Five different fin length (4.0 mm, 4.5 mm, 5.5 mm, 6.0 mm and 6.5 mm) and five different fin valleys (2, 3, 4, 5 and 6) are used in this numerical simulation. The results demonstrated that the average surface temperature, total heat transfer rate, fin effectiveness and average surface Nusselt number increased when both fin length and fin valley increased. However, the average surface heat transfer coefficient of heatsink decreased due to frictional forces when fin length increased but the average surface heat transfer coefficient of heatsink increased due to increase of exposed surface area as the fin valley increased. In conclusion, longer fin length and higher number of fin valley will provide better thermal performance in bus duct conductor.